(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is written about the important aspects of production activity in Uzbekistan. It provides enough information about the functions of this activity aimed at the development of society, especially in the sphere of culture and art, and the satisfaction of people’s spiritual needs.